Magnetic Stirrer with Speed Advisor and Timer Based on Microcontroller - I Made Aditya Nugraha; I Made Agus Mahardiananta; Putu Agus Mahadi Putra; I Gede Sura Adnyana (Journal of Robotics and Control (JRC), 2022)
A magnetic stirrer is a laboratory tool that is used to stir or mix a solution with another solution so that the solution is heterogeneous. Technology and science have now progressed, so in this study, a microcontroller-based magnetic stirrer was designed. This tool is designed with digital speed and time settings, with digital technology, it is hoped that the data reading error of the speed and time of mixing samples can be minimized, efficient in time, relatively easier to use, and produces a homogeneous solution. Based on the results of the analysis that has been carried out by a microcontroller-based magnetic stirrer in a solution with low viscosity from mixing water and syrup, it requires mixing time for 1 minute with low, medium, and high speeds. For a solution with a higher viscosity using water and special grade syrup, it takes 5 minutes at medium and high speeds. To mix water with salt and water with sugar takes 10 minutes at high speed.